Comparative Study on the Oil Content and Fatty Acids Profile among Some Brassica rapa L. Genotypes - Shelly, N. J.; Bhuiyan, M. S. R.; Rahman, J.; Zamil, S. S.; Sumon, M. M. (International Journal of Bio-resource and Stress Management, 2023)
The study was carried out at Biochemistry, Agricultural Chemistry and Environmental Science laboratory of Sher-e-Bangla Agricultural University, Dhaka, Bangladesh from March, 2020 to September, 2021 to estimate oil content and fatty acids composition of some Brassica rapa L. genotypes. The experiment was laid out in a completely randomized design with three replications and consisted of four genotypes viz., BARI Sarisha-14, Brown Special, Yellow Special, Tori-7 and their F1s. Result revealed that the oil content ranged from 34.25-45.05% among the studied genotypes. The parent, Yellow Special contained the highest amount of oil (45.05%) and Brown Special contained the lowest amount (39.48%), while among the F1s, (Brown Special×Yellow Special) contained the highest amount (39.04%) and (BARI Sar-14×Brown Special) contained the lowest amount (34.25%). The major saturated and unsaturated fatty acids content ranged from 3.92-5.42% and 92.39-93.50% respectively. The parent, Brown Special and the F1- (BARI Sar-14×Brown Special) contained the highest amount of unsaturated fatty acids (92.81%) and (93.50%) respectively, while the parent Yellow Special and the F1- (Brown Special×Tori-7) contained the lowest amount of saturated fatty acids (3.96%) and (3.92%) respectively. The highest poly unsaturated fatty acids containing parent was Tori-7 (16.98%) and F1 was Yellow Special×Tori-7 (19.27%). The erucic acid content ranged from 44.97- 54.56%. Among the parents, Tori-7 and among the F1s-Yellow Special×Tori-7 contained the lowest amount of erucic acid (44.97%) and (45.37%) respectively. Therefore, the parents and F1s with high level of poly unsaturated fatty acids and low level of erucic acid could be selected for further development of these trait.